2008
DOI: 10.1038/labinvest.3700746
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen and the liberation of placental factors responsible for vascular compromise

Abstract: Maternal endothelial activation in pre-eclampsia is attributed to the release of unknown factors from a hypoperfused placenta. To further characterize these factors, we have used a serum-free placental villous explant culture model and investigated the effect of the liberated soluble factors produced on human endothelial cell cultures. Term placental villous explants from uncomplicated pregnancies were cultured for 4 days in 20, 6 or 1% O 2 to mimic placental hyperoxia, normoxia and hypoxia. Medium collected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 52 publications
(55 reference statements)
1
24
0
1
Order By: Relevance
“…One plausible hypothesis for this role is that the hypoperfused placenta releases unknown soluble factors that contribute to maternal endothelial activation, leading to the onset of pre-eclampsia [11,12,14] . In this context, reduced NOS activity in the placenta may be a trigger for vasoconstriction therein.…”
Section: Discussionmentioning
confidence: 99%
“…One plausible hypothesis for this role is that the hypoperfused placenta releases unknown soluble factors that contribute to maternal endothelial activation, leading to the onset of pre-eclampsia [11,12,14] . In this context, reduced NOS activity in the placenta may be a trigger for vasoconstriction therein.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that the hypoxic conditions (≤5%) alter endothelial phenotype and permeability8910. We and others have shown that cultured ECs respond differently when at physiological O 2 (5–12%) compared to conventional atmospheric O 2 (21% O 2 )1112. Overall, while the individual effects of varying shear stress and O 2 tension on angiogenesis have been studied, creating an in vitro system with control over both shear stress and O 2 levels will advance our understanding and predictability of human endothelial functionality in healthy and diseased conditions.…”
mentioning
confidence: 99%
“…We have recently used a hypoxic placental explant model to study factors present in serum-free explant-conditioned media and their effect on endothelial cell function. 48 Factors capable of altering endothelial function were demonstrated in explant-conditioned media generated from placental explants cultured under hypoxic conditions (1% vs 6% O 2 ) using several different endothelial bioassays. In our laboratories, we have used a MS-based approach to identify differences in proteins released into placental explant-conditioned media under normoxic and hypoxic conditions.…”
Section: Used 2-de and Lc/ms/msmentioning
confidence: 99%